The Influence of ICT Integration on ELT in Higher Education: A Systematic Literature Review - Heriyanto, Eko; Hartono, Rudi; Wahyuni , Sri (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2025)
This study aimed to discuss the integration of Information and Communication Technology (ICT) in English Language Teaching (ELT) in higher education based on a systematic review of several relevant articles. The articles analyzed include studies regarding teachers’ knowledge and experiences regarding the use of ICT in English language teaching, as well as the challenges and potential associated with implementing these technologies in the classroom. The findings show that although many teachers, both novice and experienced, show high confidence in using ICT tools, difficulties in pedagogical application and lack of practical training are the main barriers. Some other inhibiting factors are a lack of access to technology, limited infrastructure, and resistance to change among more experienced educators. This article suggests a more holistic approach in preparing educators for ICT integration, including improved professional training focusing on developing pedagogical skills in ICT use and stronger institutional support. Although these challenges are significant, the potential of ICT in improving student engagement and learning outcomes suggests that effective technology integration can significantly impact English language teaching in higher education.